Infrared second-order nonlinear optical effect in Sb2Te3–SrBr2–PbCl2 glass - Gruhn, Wojciech (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
A phenomenological and microscopic theory of IR picosecond nonlinear optical response in glass is developed for the middle IR spectral range (5–15 mm). Both IR-induced second harmonic generation (SHG) as well as linear electrooptic effect (LEOE) were observed. The observed effects are explained within a framework of fifth-order nonlinear optical susceptibilities. A model that reproduces the basic features of the experimental data, in which are discovered the optical nonlinearities caused by photoinduced electron–phonon anharmonic interactions, is proposed. The role of the IR induced phase matching conditions in the observed phenomena is discussed.
Optica Applicata, Vol. 35, 2005, nr 3, s. 329-337
Keywords: optyka; photoinduced second harmonic generation; Sb2Te3–SrBr2–PbCl2 glass